The effects of caffeine ingestion on time trial cycling performance - Mc Naughton, L. R.; Lovell, R. J.; Siegler, J. C.; Midgley, A. W.; Sandstrom, M.; Bentley, D. J. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. The purpose of this work was to determine the effects of caffeine ingestion on cycling time trial (TT) performance in well trained male subjects. Methods. Eight males, with the following physical characteristics (Mean ± SD) age 30.2±10.1 years, height 180.3±7.1 cm, mass 70.4±5.1 kg, V.O2max 63.6±4.4 mL/kg.min undertook three 1 h TT performances on a VelotronPro® cycle ergometer, in a double blind, random fashion. The trials were Control (C), Placebo (Pl) and Caffeine (CAF). The CAF and Pl were given 60 min prior to exercise in a dose of 6 mg/kg body mass. Prior to ingestion, 60 min post ingestion, and at the end of the TT, subjects gave 10 mL of venous blood which was analysed for lactate, glucose, and free fatty acids. Expired air was collected throughout each test by indirect calorimetry. Results. The cyclists rode significantly further in CAF trial (28.11±1.32 km) than they did in the C (26.69±1.5 km, P<0.03) or Pl (27.0±1.5 km, P<0.03) trials. No significant differences were seen between C and Pl trials (P>0.88). No differences between C and Pl were seen in heart rate data throughout the TT (p>0.05). The free fatty acid (FFA) concentrations were significantly higher in the CAF trials both post ingestion (P<0.005) and post exercise (P<0.0001) than either C or Pl trials. Conclusion. We concluded that performance was improved possibly based upon a greater reliance on fat metabolism, as indicated by increased FFA and a lower respiratory exchange ratio (RER).